Morphometric Study and Sex Ratio of Mediterranean Lobsters Scyllarides latus in the Syrian Shore - عمار , ازدهار; عيد, أيهم (Latakia University Journal -Biological Sciences Series, 2021)
The aim of this research is to study the morphometric and morphometric characteristics of Scyllarides latus in the natural marine environment, and to determine the sex ratio (males: females) in the marine natural environment as an introduction to hatching and cultivation. Individuals of the species were collected monthly from the Syrian marine waters at the coast of Latakia during the period extending from the month of December The second, until December 2019. The laboratory study included distinguishing between males and females for all individuals, conducting morphometric measurements for them, determining weight, and then conducting correlation coefficients between the readings taken. It was found that females accounted for 44% of the total number, and their length ranged between 172 - 323 mm, where the group with lengths 200 - 250 mm dominated, while the percentage of males reached 56%, and their length ranged between 172-320 mm. The lengths are 200 - 250 mm. The weights of the males ranged between 168.6-717g, and the weights of the females ranged between 207.2-769g. Two periods of control were observed between males and females. Females dominated the sample from December to April, while males dominated the sample from May to November. The results of this study indicate the suitability of the characteristics of the marine environment in the study area for the growth and reproduction of the studied species. We recommend encouraging work on its cultivation and cultivation by private or public bodies such as the Public Authority for Fish Resources.